Detecting Mispronunciations of Non-Native (L2) Post-Graduate Students of English Language Education in Indonesia - Syahfitri Purnama; Muhammad Ali Pawiro; Azis Azis (Universitas Negeri Makassar, 2023)
Speaker’s good pronunciation makes his/her listener comfortable, and confident to participate in the conversation and his/her mispronunciations bring implications to the listener’s awareness and involvement with the message spoken. The research was aimed at detecting the mispronunciations made by 70 non-native (L2) post-graduate students who were enrolled in the English department and were also school teachers in Greater Jakarta (including Jakarta, Bogor, Depok, Tangerang, and Bekasi [or commonly shortened as Jabodetabek]). They were given English texts to read, and recorded, and a semi-structured interview was applied. Error analysis was employed to check mispronunciations. The results showed that 43 students (61%) made mispronunciations and 27 (39%) didn’t. Mispronunciation was found on vowels by 4 students (5.71%), on consonants by 5 (7.14%), on diphthongs by 3 (4.28%), and on consonant clusters by 14 (20%). Most of the students made intralingual and global errors.